2014
DOI: 10.1155/2014/720181
|View full text |Cite
|
Sign up to set email alerts
|

Perforation of the Pregnant Uterus during Laparoscopy for Suspected Internal Herniation after Gastric Bypass

Abstract: We report perforations of a pregnant uterus during laparoscopy for suspected internal herniation after gastric bypass at 24 weeks of gestation. Abdominal access and gas insufflation were achieved by the use of a 12 mm optic trocar. An additional 5 mm trocar was positioned. The perforations were handled by suturing following laparotomy and mobilisation of the high located uterus. The uterine fundus was located in the subcostal area. Internal herniation was not verified. A cesarean section was made 6 weeks later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Buser 4 published a retrospective analysis of 36 laparoscopic surgeries performed on pregnant women over a 12-year period by a single surgeon and noted one case that was complicated by uterine perforation during placement of a blunt trocar. Mala et al 5 described a case of a pregnant woman undergoing laparoscopy at 24 weeks' gestation due to concern for internal herniation of her roux-en-Y gastric bypass. During laparoscopic entry with an optical trocar, the gravid uterus was inadvertently perforated and a fetal foot could be seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buser 4 published a retrospective analysis of 36 laparoscopic surgeries performed on pregnant women over a 12-year period by a single surgeon and noted one case that was complicated by uterine perforation during placement of a blunt trocar. Mala et al 5 described a case of a pregnant woman undergoing laparoscopy at 24 weeks' gestation due to concern for internal herniation of her roux-en-Y gastric bypass. During laparoscopic entry with an optical trocar, the gravid uterus was inadvertently perforated and a fetal foot could be seen.…”
Section: Discussionmentioning
confidence: 99%
“…During laparoscopic entry with an optical trocar, the gravid uterus was inadvertently perforated and a fetal foot could be seen. 5 Friedman et al 6 reported another case in which a 21-week pregnant uterus was punctured with a Veress needle which resulted in spontaneous rupture of membranes and subsequent loss of the pregnancy. These cases highlight the need for obstetricians to be involved in preoperative planning of pregnant patients undergoing laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%